Endoscopic Endonasal Transphenoidal Surgery Using the BrainLAB® Headband for Navigation Without Rigid Fixation - Duque, Sara G.; Gorrepati, Ramana; Kesavabhotla, Kartik; Huang, Clark; Boockvar, John A. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
The number of lesions of the skull base currently resected via endoscopic, endonasal, transphenoidal approach has increased. We have successfully treated 63 consecutive patients with pituitary lesions using this technique in combination with BrainLAB reference headband and laser surface scanning (BrainLAB®, Heimstetten, Germany) for surgical navigation. This technique affords several advantages over neuronavigation based on adhesive-mounted fiducial registration. Rigid fixation in a Mayfield clamp is not required, which allows for flexibility with respect to positioning of the head during the procedure. This is particularly important, as extension and flexion of the head provide greater exposure to the clivus and anterior skull base, respectively. Also, we demonstrate that this technique is safe, easy-to-use, and faster compared with other ones.
Keywords: pituitary surgery; endoscopic surgery; headband; neuronavigation